THE RELATIONSHIP OF INVALIDITY OF LEGAL TRANSACTIONS AND SUBSIDIARY LIABILITY OF CONTROLLING PERSONS - AMBARTSUMOV R.A.; PETUHOV S.V. (Legal Bulletin)
The relevance of the article is due to the fact that contesting the debtor's transactions and subsidiary liability of controlling persons are among the few effectively operating institutions within the framework of bankruptcy legislation. In turn, the establishment of provisions that exclude legal uncertainty in their use is a priority for the entire civil turnover. The purpose of the study is to determine the connecting elements of institutions challenging the debtor's transactions and subsidiary liability of controlling persons. The main problem is the unreasonably large-scale use of evaluative concepts, which significantly complicate the consistency of the law enforcement officer when using the institutions in question. Research methods. Analysis, synthesis, formal legal and comparative legal methods Conclusions. The fundamental "points of contact" of the institutions of contesting the debtor's transactions and subsidiary liability of controlling persons have been identified. The article points out the ambiguity of the practice of expanding judicial discretion, and also gives an assessment of future novels in the field of challenging the "chain of transactions".